1997
DOI: 10.1016/s0022-5347(01)64487-2
|View full text |Cite
|
Sign up to set email alerts
|

Radical Cystectomy for Carcinoma of the Bladder: Critical Evaluation of the Results in 1,026 Cases

Abstract: Contemporary cystectomy with continent diversion for muscle invasive disease provides minimal morbidity, offers good locoregional disease control and results in acceptable quality of life. The presence of positive regional lymph nodes is not a contraindication to this therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
210
3
12

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(247 citation statements)
references
References 42 publications
22
210
3
12
Order By: Relevance
“…A 3% mortality rate in the present series is comparable with other contemporary series of radical cystectomy [12,15,16]. Furthermore, preoperative therapy (radiation and/or chemotherapy), and the form of urinary diversion used (continent or incontinent) does not apparently alter the mortality rate.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…A 3% mortality rate in the present series is comparable with other contemporary series of radical cystectomy [12,15,16]. Furthermore, preoperative therapy (radiation and/or chemotherapy), and the form of urinary diversion used (continent or incontinent) does not apparently alter the mortality rate.…”
Section: Discussionsupporting
confidence: 72%
“…There was also a significant difference when stratifying patients by their p-stage; patients with lymph nodepositive disease and organ-confined bladder tumours had a significantly better recurrence-free survival than those with extravesical, lymph node-positive tumours. Similar results with lymph node-positive disease after cystectomy have been reported [12,13,15,18,19].Several studies recently suggested that the number of lymph nodes involved with tumour [18][19][20][21][22], and the extent of the lymph node dissection [18,20,21] are important variables for patients undergoing cystectomy for bladder cancer. We recently re-examined 246 patients with lymph node tumour involvement after radical cystectomy (data not presented) [23] to evaluate other prognostic factors in this high-risk group of patients.…”
supporting
confidence: 75%
“…The prevalence is reported to be considerably higher in the developing world, accounting for up to 11% [6]. In a series by Ravi et al from India, out of 21 non-urothelial tumours, 9 (42.8 %) were adenocarcinoma with a mean age of 49.33 years [2].…”
Section: Adenocarcinoma Of the Bladdermentioning
confidence: 98%
“…1 Despite improvements in surgical technique, anesthesia and perioperative care, radical cystectomy is still associated with greater morbidity and prolonged in-patient stay after surgery than other urological procedures. Overall complication rates have been reported as high as 64% at 90 days, 2 with an average in-patient stay of 17.4 days.…”
Section: Introductionmentioning
confidence: 99%